Carlito's Way - Torres, Edwin 1931-; Koepp, David 1963- (Studiocanal GmbH, 2023)
After getting out of jail, a Puerto Rican drug lord wants to go straight, but his cohorts in the New York Underworld won't let him.
Orig.: USA 1993
Digital remastered
Extras: Making Of; Deleted scenes; Trailer
Keywords: Crimen organizado - Nueva York (Estados Unidos) - Nueva York - Teatro; Delitos - Nueva York (Estados Unidos) - Nueva York - Teatro; Criminal behavior -- New York (State) -- New York -- Drama; Ex-convicts -- New York (State) -- New York -- Drama; Organized crime -- New York (State) -- New York -- Drama; Crime films; Bandenkriminalität; Organisiertes Verbrechen; Melodrama; Verfilmung; Spielfilm; New York, NY; Film; DVD-Video; Feature films; Video recordings for the hearing impaired; Crime - Feature